2016
DOI: 10.1038/eye.2016.132
|View full text |Cite
|
Sign up to set email alerts
|

Difluprednate versus prednisolone acetate for inflammation following cataract surgery in pediatric patients: a randomized safety and efficacy study

Abstract: PurposeTo evaluate safety and efficacy of difluprednate 0.05% ophthalmic emulsion for treatment of postoperative inflammation after cataract surgery in pediatric patients.MethodsThis was a phase 3B, multicentre, randomized, double-masked, active-controlled study of patients aged 0–3 years who underwent uncomplicated cataract surgery in one eye, with/without intraocular lens implantation. Patients were randomized to receive difluprednate 0.05% four times daily or prednisolone acetate 1% for 14 days post surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 21 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…As for the theory of cataract surgery-related inflammation, intraocular inflammation is common after cataract surgery. The inflammatory response occurs when the bloodaqueous barrier is compromised, thus increasing vascular permeability changes associated with inflammation and oedema (Modi et al 2014;Wilson et al 2016). Inflammation induced by cataract surgery may exacerbate the rate of AMD progression (Donoso et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As for the theory of cataract surgery-related inflammation, intraocular inflammation is common after cataract surgery. The inflammatory response occurs when the bloodaqueous barrier is compromised, thus increasing vascular permeability changes associated with inflammation and oedema (Modi et al 2014;Wilson et al 2016). Inflammation induced by cataract surgery may exacerbate the rate of AMD progression (Donoso et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study of post-cataract surgery pediatric patients (0–3 years old) compared DFBA and PA and found similar safety and efficacy profiles between the two corticosteroids 31. Patients received a regimen of either DFBA or PA QID for 14 days, followed by a 14 day taper.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Several studies have demonstrated that topical steroids are safe and effective in reducing ocular inflammation when administered during surgery and throughout the immediate 4 weeks following cataract extraction. 8,9 Difluprednate ophthalmic emulsion is a topical ocular corticosteroid that has been approved by the US Food and Drug Administration (FDA) since 2008 as treatment for the inflammation and pain associated with ocular surgery. 4,7,[9][10][11] However, in Mexico and Latin America, it is not currently commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Difluprednate ophthalmic emulsion is a topical ocular corticosteroid that has been approved by the US Food and Drug Administration (FDA) since 2008 as treatment for the inflammation and pain associated with ocular surgery. 4,7,[9][10][11] However, in Mexico and Latin America, it is not currently commercially available. Difluprednate is an ophthalmic steroid with high glucocorticoid receptorbinding affinity and high tissue penetration, therefore it is considered more potent than other topically applied steroids.…”
Section: Introductionmentioning
confidence: 99%